Analysis and evaluation of battery-supercapacitor hybrid energy storage system for photovoltaic installation. (7th December 2016) - Cabrane, Zineb; Ouassaid, Mohammed; Maaroufi, Mohamed
Abstract: Standalone operation of a photovoltaic generating system under fluctuating solar irradiance and variable load conditions necessitates a storage energy unit. The energy storage system by using battery–supercapacitor combination is an interesting solution. However, batteries have a high energy storage ratio but are limited in the power. In the other hand, supercapacitors can provide high levels of power while they have a much lower energy storage ratio. Moreover, the SC can act as a buffer against large magnitudes and rapid fluctuations in power. In this paper, supercapacitors are used to reduce stresses on batteries and improve their life cycle. In this context, the performance of the RMS current gain in battery, the gain in energy losses, the total energy efficiency and the elimination rate of surge load power are explored, in different operating state conditions. These parameters are also investigated versus the SCs cost. All tests are carried with different number of parallel supercapacitors and the filter constant.